Stealth Conflicts: Unpacking the Causes of Underreported and Invisible Wars - Konecna, Lucie (Journal of Regional Security, 2024)
This study aims to identify the necessary and sufficient conditions that contribute to categorizing certain conflicts as "stealth," meaning significant yet underreported or overlooked, as opposed to conflicts well-covered by the media. Focusing on cases in Asia and Africa from 2014 to 2024, the research employs qualitative comparative analysis (QCA) to assess six conditions for the conflict to be recognized as a stealth conflict derived from Hawkins’ theory which explains that conflicts are overlooked when key actors (policy makers, media, the public, and academia) are not engaged due to factors such as national/political interest, geographic proximity and access, ability to identify with conflict participants, ability to sympathize with victims, simplicity (how easy it is to understand a conflict) and sensationalism (involves events that are dramatic and attention-grabbing). Our findings suggest that a lack of simplicity and limited sensationalism are key factors in hindering the visibility of conflicts, especially in regions like West Papua and Balochistan. The analysis reveals that there are two necessary conditions and three sufficient conditions that influence the visibility of conflicts.